Acute stress can boost and buffer hedonic consumption: The role of individual differences in consumer life history strategies. (February 2022) - Fennis, Bob M.; Gineikiene, Justina; Barauskaite, Dovile; van Koningsbruggen, Guido M.
Abstract: Mixed findings on the relationship between acute stress and the tendency to engage in hedonic food consumption suggest that stress may both boost and buffer hedonic eating. The present research aims to contribute to reconciling these mixed findings by focusing on the role of individual differences in consumer life history strategies (LHS) –short-term, impulsive, reward-sensitive (fast) vs. long-term, reflective, goal-oriented (slow) self-regulatory strategies– that might drive hedonic eating. We propose and show that stress may boost hedonic consumption among fast LHS consumers, while the relationship is buffered (non-significant) among their slow LHS counterparts. Moreover, we find that this stress-induced eating among fast LHS consumers is also cue-driven such that fast (but not slow) LHS consumers show a higher sensitivity to scarcity cues signaling the desirability of a palatable food under conditions of stress. Finally, we find that a cue indicating a high caloric content of the food may curb the tendency for fast LHS consumers to engage in (over) consumption of hedonic foods under stress. Highlights: Life history strategies (LHS) shape when stress may boost and buffer hedonic eating. Fast LHS consumers show higher sensitivity to food scarcity cues under stress. Fast LHS consumers show higher sensitivity to calorie warning cues under stress. Results illuminate when and why stress fosters (over)eating. Results suggest what types of nudges may promote or curb such behavior.